(3EZGKI GddgaGf aj eUGFO GdTjWGfs - (3eMeO Hf CHj HcQ Hf CjhH Hf bje GdLhRjg, GHf Gdbje, TeS GdOjf, CHh YHO Gddg, J (B751 (3g` s ((3Ydi Hf G Ydi Hf CHj HcQ Hf YeQ GdebOSi s)
(3ChdgG (B:s
(3QHfG BJfG ef dOfc QMeI hgjF dfG ef CeQfG QTOG hUdi Gddg Ydi SjOfG eMeO hBdg GdMeO ddg GdPi XgQ dChdjGFg HfYeJ LdGdg hGfGQ bdhHge HeTGgOI UaGJ ceGdg s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3HgG fXGe GdJYbjHIs
(3Ydi UaMI GdYfhGf Jedcs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56s
Keywords: (3GdJUha hGdBOGH GdTQYjIs